Trap volcanism of Siberia and «the Permian-Triassic extinction» - G. N. Sadovnikov (Известия высших учебных заведений: Геология и разведка, 2016)
During the entire period of volcanism in Siberia the biota was diverse. Dominants among the plants are Acrostichides, Boreopteris, Cladophlebis, Cordaites, Dzergalanella, Elatocladus, Lepidopteris, Madygenia, Maria, Mertensides, Neocalamites, Osmundopsis, Paracalamites (?), Parajacutiella (?), Pecopteris, Phyllotheca, Pleuromeia, Pursongia, Quadrocladus, Rhipidopsis, Todites, Tomia, Tomiostrobus, Voltzia (?), Yavorskyia. Within the Conchostraca the dominants were Bipemphigus, Echinolimnadia, Falsisca, Limnadia. Neither the beginning of trap volcanism (Vishkilian), nor the increase of tuffs eruptions (Lebedev time), nor increasing lava effusions by reducing the ejection of tuffs (Hungtukun time), nor complete replacement of the tuffs eruptions by lavas (Putorana time) result in an reduction of the biotic diversity in the volcanic area. On the contrary, the diversity was steadily growing. In the Induan (Otoceras boreale phase) the diversity decreased, but it was outside the volcanic plateau. The biotic crisis by the model of A.S. Alekseev on the volcanic plateau is absent. Therefore, a direct link in the changes in biota at the Permian-Triassic boundary and volcanism is unlikely.